Outdoor Program Based Counseling to Improve Interpersonal Relationship between Special Teachers and Parents of Children with Special Needs in Inclusive School - Arifiana, Isrida Yul; Leonadi, Tino (Budapest International Research and Critics University, 2021)
This study aims to see whether the Outdoor Program Based Counseling method effectively improves interpersonal relationships between Special Assistant Teachers and Parents of Children with Special Needs. This research is quantitative research with an experimental method. Subjects in the study were divided into a control group and an experimental group. Subjects in the experimental group were 28 people. The data obtained in this study used a scale, observation, and interviews which were used as complementary data. The statistical analysis results using the Mann Whitney technique, the significance value obtained is p = 0.004, which means it is smaller than 0.05 (0.004 <0.05). From this value, it can be concluded that the Outdoor Based Counseling Program effectively improves the interpersonal relationships of special assistant teachers and parents of children with special needs in inclusive school. From the calculation of effect size, it can be concluded that the effect of Outdoor Based Counseling Program activities on improving interpersonal relationships has a moderate effect. This situation can be caused by several influencing factors such as the influence of the physical environment and nature on the activities carried out, the characteristics of the trainer or facilitator, the grasping power of the debriefing process, as well as attitude towards activities and awareness of their role as parents or teachers.